Correction to: Financial crisis and income-related inequalities in the universal provision of a public service: the case of healthcare in Spain - Ignacio Abásolo; Marc Saez; Guillem López-Casasnovas (BMC, 2019)
Following publication of the original article [1], the autor reported 5 references should be indicated in Spanish. The correct references can be found below: